Cities and the Sea Level - Yatang Lin; Thomas K. J. McDermott; Guy Michaels (Institute of Labor Economics (IZA), 2021)
Construction on low elevation coastal zones is risky for both residents and taxpayers who bail them out, especially when sea levels are rising. We study this construction using spatially disaggregated data on the US Atlantic and Gulf coasts. We document nine stylized facts, including a sizeable rise in the share of coastal housing built on flood-prone land from 1990-2010, which concentrated particularly in densely populated areas. To explain our findings, we develop a model of a monocentric coastal city, which we then use to explore the consequences of sea level rise and government policies.
Keywords: R11; Q54; R14; 330; cities; climate change; sea level rise